Towards developing a test method for military pelvic protection*. Issue 10 (3rd October 2018) - Saunders, Christopher; Carr, Debra
Abstract: Prior to adoption of the pelvic protection system (PPS), one of the signature injuries suffered by H.M. Armed Forces who served in Afghanistan was caused by buried improvised explosive devices (IEDs) accelerating secondary fragmentation from the ground environment into the groin, perineum, genitals, buttocks and legs of personnel. In the current work, a test method was developed which considered the combined effects of explosive blast and fragment loading of targets of Tier 2 PPS. The work identified that it is possible to explosively propel fragments of the ground environment into the specimens of Tier 2 PPS and to analyse each specimen. In doing so, a scenario peculiar to the IED threat faced in Afghanistan was able to be replicated. Such work allows insights into injuries suffered and will assist in the development of future protective clothing systems that require dual blast and fragment protective properties.